Diagnostic Accuracy of Con Beam Computed Tomography in Detection of Dental Root Fraction in Comparing with Conventional Scanning and Real Samples After Extracting - Zainab A.H. Al-Tamemi; Jabbar jasim Kareem (Genius Journals, 2022)
When a tooth has extensive root fracture, the prognosis is not good, and tooth extraction is frequently the only treatment option that can be considered at this point. Accurate diagnosis is essential to avoid unnecessary and inappropriate treatment. The aim of this study was to compare the cone beam CT diagnostic accuracy with the traditional dental scanning and extracted teeth. Root canal fillings' impact on root fracture detection was also studied. 100 cases with suspected root fractures were evaluated using a preestablished scoring system. Direct visualization of each extracted tooth and its colorization determined final patient results. 55 of 100 patients had non-endodontically treated teeth, while 45 were treated with the endodontics. The findings revealed that the cone beam CT has a high diagnostic accuracy when it comes to the detection of root fractures. Cone beam CT was superior to dental radiography in terms of its ability to detect root fractures (P value, 0.001). Root canal fillings lower the sensitivity of cone beam CT scans but do not affect their specificity. The sensitivity and specificity of dental radiography were not affected in any way by root canal fillings. In conclusion, when it comes to the detection of root fractures in patients who have been treated with nonendodontic or endodontic methods, cone beam CT appears to be more accurate than conventional dental scanning
Keywords: computed tomography; con beam; root fracture; conventional scanning